background image

5.33. FUNCTION SPACES OF POSETS

116

Proposition

651

.

If each (

A

i

,

Z

i

) where

i

n

(for some index set

n

) is a

down-aligned filtrator with separable core then (

Q

A

,

Q

Z

) is with separable core.

Proof.

Let

a

6

=

b

. Then

i

n

:

a

i

6

=

b

i

. So

x

Z

i

: (

x

6

a

i

x

b

i

) (or

vice versa).

Take

y

=

λj

n

:

(

x

if

j

=

i

A

j

if

j

6

=

i

. Then we have

y

6

a

and

y

b

and

y

Z

.

Proposition

652

.

Let every

A

i

be a bounded lattice. Every (

A

i

,

Z

i

) is a

central filtrator iff (

Q

A

,

Q

Z

) is a central filtrator.

Proof.

x

Z

Y

A

y

Y

A

: (

x

u

y

=

Q

A

x

t

y

=

>

Q

A

)

y

Y

A

i

dom

A

: (

x

i

u

y

i

=

A

i

x

i

t

y

i

=

>

A

i

)

i

dom

A

y

A

i

: (

x

i

u

y

=

A

i

x

i

t

y

=

>

A

i

)

i

dom

A

:

x

i

Z

(

A

i

)

.

So

Z

Y

A

=

Y

Z

Y

i

dom

A

Z

(

A

i

) =

Y

Z

(because every

Z

i

is nonempty)

⇔ ∀

i

dom

A

:

Z

(

A

i

) =

Z

i

.

Proposition

653

.

For every element

a

of a product filtrator (

Q

A

,

Q

Z

):

1

. up

a

=

Q

i

dom

a

up

a

i

;

2

. down

a

=

Q

i

dom

a

down

a

i

.

Proof.

We will prove only the first as the second is dual.

up

a

=

c

Q

Z

c

w

a

=

c

Q

Z

i

dom

a

:

c

i

w

a

i

=

c

Q

Z

i

dom

a

:

c

i

up

a

i

=

Y

i

dom

a

up

a

i

.

Proposition

654

.

If every (

A

i

n

,

Z

i

n

) is a prefiltered filtrator, then

(

Q

A

,

Q

Z

) is a prefiltered filtrator.

Proof.

Let

a, b

Q

A

and

a

6

=

b

. Then there exists

i

n

such that

a

i

6

=

b

i

and so up

a

i

6

= up

b

i

. Consequently

Q

i

dom

a

up

a

i

6

=

Q

i

dom

a

up

b

i

that is up

a

6

=

up

b

.

Proposition

655

.

Let every (

A

i

n

,

Z

i

n

) be a filtered filtrator with up

x

6

=

for every

x

A

i

(for every

i

n

). Then (

Q

A

,

Q

Z

) is a filtered filtrator.

Proof.

Let every (

A

i

,

Z

i

) be a filtered filtrator. Let up

a

up

b

for some

a, b

Q

A

. Then

Q

i

dom

a

up

a

i

Q

i

dom

a

up

b

i

and consequently (taking into

account that up

x

6

=

for every

x

A

i

) up

a

i

up

b

i

for every

i

n

. Then

i

n

:

a

i

v

b

i

that is

a

v

b

.